MEWUJUDKAN LEMBAGA KEUANGAN MIKRO SYARIAH BERBASIS LABORATORIUM - Aisyah, Esy Nur; Siswanto, Siswanto Siswanto; Rahayu, Yayuk Sri (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Educational institutions have a challenge to improve the quality of graduates who are highly competitive namely graduates who are able to adapt quickly to the work environment. This is a key indicator of the â€œlinks and matchâ€ between human resources need and education laboratories. The role of the real laboratory is very important to be used as a learning resource for Islamic banks as well as a medium of socialization or education within the scope of the academic community. This paper seeks to provide an overview based on the author's experience to realize or establish a real transaction laboratory for El-dinar Finance House, starting from the pioneering stage to the technical implementation which is synergized with the student learning model.